Gestión organizacional una mirada desde la investigación - Cocuy Espinosa, Julián; Rengifo Rentería, Carlos Lino; Contreras Gamboa, Erika Andrea; Duque Ceballos, Jose Luis; Hurtado Ayala, Andrea; Giraldo Patiño, Claudia Lorena; Rodríguez Rivera, Pablo César; Duque Ramírez, Sandra Patricia; Castañeda Vargas, María Elena; Arboleda Castro, María Elvira; Parra Cerón, Valeria; Basante Bastidas, Oscar Esteban; et al. (Universidad Santiago de Cali, 2025)
Published